Edoughnura rara n.gen., n.sp., an enigmatic genus of Neanurinae Collembola from the Edough Massif (Algeria) - Deharveng, Louis; Kroua, Salah Hamra; Bedos, Anne (Zootaxa, 2007)
A new genus and new species of Neanurinae Collembola, Edoughnura rara, is described from the Edough massif in Algeria. It combines a number of unusual or unique features : additional chaetae on head; mandible as a long, thin, ciliated lamella; chaetae Di of Th. II-III in line; tubercles Di fused on axis from Abd.III to Abd.V. Its affinities within the tribe Neanurini remains obscure.